2021
DOI: 10.21776/ub.habitat.2021.032.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting The Food Security of The Bajo Community Households In West Muna District During The Covid-19 Pandemic

Abstract: This study aims to determine the factors that affect the household food security of the Bajo community in Napano Kusambi Sub District. The research was conducted in Napano Kusambi Sub District, West Muna District, the selection of the research location was carried out deliberately (Purposive), with the consideration that the village is a coastal village with many Bajo community settlements, most of whom work as fishermen. The population in this study were all the Bajo people in Napano Kusambi Sub District, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Meanwhile, the factors that influence household food security are education, age, smoking habits, number of household members, rural residence, and employment as farm laborers. Different from Limi et. al., (2021), food security is influenced by income, the age of the head of the household, and the age of the housewife.…”
Section: Theoretical Underpinningmentioning
confidence: 68%
“…Meanwhile, the factors that influence household food security are education, age, smoking habits, number of household members, rural residence, and employment as farm laborers. Different from Limi et. al., (2021), food security is influenced by income, the age of the head of the household, and the age of the housewife.…”
Section: Theoretical Underpinningmentioning
confidence: 68%
“…The study employed a binary logistic regression model to identify the factors influencing home food security in the Bajo community within the Napano Kusambi Sub District. The findings demonstrated that the variables that substantially affected the food security of households were Household earnings, the age of the household leader, and the age of the female head of the household (Limi, Zani, & Selvi, 2021).…”
Section: Methodsmentioning
confidence: 97%
“…If the income increases, the opportunity for consumption will increase. In addition, a high-income level will increase food security and vice versa (Limi et al, 2021).…”
Section: Income Analysismentioning
confidence: 99%
“…A number of factors influence household food security, including household head education, the size of the household (Ruhyana et al, 2020) Source: Primary Data, 2021 (Processed) (Drammeh et al, 2019), rice expenditure (Safitri et al, 2017), and maternal education (Limi et al, 2021).…”
Section: Factors That Affect the Energy Adequacy Ratementioning
confidence: 99%